1991
DOI: 10.1172/jci115381
|View full text |Cite
|
Sign up to set email alerts
|

Altered transcriptional regulation of phosphoenolpyruvate carboxykinase in rats following endotoxin treatment.

Abstract: The molecular mechanism involved in altered regulation of the rate-limiting enzyme in hepatic gluconeogenesis, phosphoenolpyruvate carboxykinase (PEPCK), during endotoxemia is not completely understood. We examined, therefore, the effect of a nonlethal dose of Escherichia coli endotoxin on PEPCK gene expression in fasted rats. 5 h after endotoxin treatment, the PEPCK transcription rate and the amount of mRNAPEI'K were significantly decreased at a time when the insulin/glucagon (I/ G) molar ratio and plasma cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
2
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 38 publications
2
42
2
1
Order By: Relevance
“…Although IL-6 administration affects neither the regulation of gluconeogenesis nor the expression of hepatic PEPCK, it is capable of inhibiting glucagoninduced expression and activation of PEPCK [84]. This may suggest that IL-6 can actually improve hepatic insulin resistance in patients with Type 2 diabetes.…”
Section: Interaction Between Il-6 and Glucose Transport In Vivomentioning
confidence: 99%
“…Although IL-6 administration affects neither the regulation of gluconeogenesis nor the expression of hepatic PEPCK, it is capable of inhibiting glucagoninduced expression and activation of PEPCK [84]. This may suggest that IL-6 can actually improve hepatic insulin resistance in patients with Type 2 diabetes.…”
Section: Interaction Between Il-6 and Glucose Transport In Vivomentioning
confidence: 99%
“…The DNA fragment was generated by polymerase sion. 23,24 chain reaction with primers 5 CAAGTGTAGCCCAGTAGAAC3…”
mentioning
confidence: 99%
“…The encoded protein may serve a similar function, although it is constitutively expressed and not modulated by the hormones, including glucagon and insulin, that regulate the cytosolic form. Hill et al reported that the direct action of TNF to decrease the PEPCK transcription rate was confirmed in vitro with H-4-II-E Reuber hepatoma cells (24). The authors suggested that PCK2 may be associated with hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 98%